PENYELESAIAN PERMASALAHAN PENENTUAN RUTE KENDARAAN PENGANTARAN DAN PENGAMBILAN SIMULTAN DENGAN JENDELA WAKTU PADA KASUS CV BUTITIA - Pundi Satrio, Anggaputra
CV Butitia is a company engaged in the ornamental plant industry, one of the fastest growing services is the ornamental plant rental service. The management feels that the profits generated by this service are not maximized and that cost savings are needed in order to generate a larger margin. CV Butitia requires a distribution planning method to be proposed for plant rental activities that can replace the role of operational managers’ intuition in planning rental plant distribution to minimize transportation costs. This study discusses the vehicle routing problem with simultaneous pickup and delivery with time window (VRPSPDTW) to minimize transportation costs. A mathematical model was developed to produce a solution route plan by determining the order of customers and freight loads based on each customer's delivery and pickup requests. The company need program that are easy to use and efficient in terms of computational time. Thus, an solution was developed in VBA Microsoft Excel using a heuristic sequential insertion algorithm. The algorithm built can produce a solution that can result in an average transportation cost savings of 16.88% compared to the existing route. In addition, the efficiency of the number of routes is 8.33%. The sequential insertion algorithm produces a local optimum solution with a computation time of less than one second, this heuristic output produces a better route when compared to current conditions.